Exploratory Field and Laboratory Investigation on the Use of Noncontact Digital Ski Sensor in the South Korea Expressway Network - In Bae Kim; Ki Hoon Moon; Augusto Cannone Falchetto (Advances in Civil Engineering)
In the case of asphalt pavement construction, better smoothing and reliable material performance acquisition are essential. In South Korea, the next-generation asphalt pavement-smoothing technology, known as the noncontact digital ski (NCDS), started to be used in expressway construction in 2018, making this system an essential tool in the paving industry. The present work thoroughly assessed how employing the NCDS system affected the response of the pavement material at low temperatures. Portions of paved roads with and without NCDS were assessed for the international roughness index (IRI, m/km). The development of thermal stress propagation was then examined using the bending beam rheometer on asphalt samples from the road. Based on straightforward visual and statistical analysis, it was discovered that using NCDS produces significantly lower IRI and reduced thermal stress, which raises the possibility that using NCDS has the potential for better low-temperatures predictions.